The Degree of Practicing Technological Competencies by School Principals in Jordan in the Light of the Standards of the International Society for Technology in Education (ISTE) and its Relation to the Organizational Creativity from their Point of View - Abbasi , Dina K.; Arouri, Yousef M. (Dirasat: Educational Sciences, 2024)
Objectives: This study aims to investigate the extent to which school principals in Jordan practice technological competencies in light of the International Society for Technology in Education (ISTE) standards, and to explore their organizational creativity from their perspective. Additionally, the study examined the relationship between technological competencies and organizational creativity. Methods: Descriptive and correlational methodologies were employed to address the study’s questions. The study tools were applied after verifying their validity and reliability on a sample of 331 school principals in Jordan. Results: The study’s results revealed that the degree of practicing technological competencies and organizational creativity was high among the study sample. There was a statistically significant relationship between the practice of technological competencies and organizational creativity, with a Pearson correlation coefficient of (.627), considered moderate. Conclusions: The study recommends that school principals enhance and develop their technological competencies in accordance with the ISTE standards, as it contributes to improving their organizational creativity, leadership capabilities, and the empowerment of schools, connecting them to the digital world. The study’s findings open up avenues for further research on the impact of suggested variables, such as the number of technology-related training courses and the learning environment, whether governmental or private, on the relationship between technological competencies and organizational creativity.